PENINGKATAN PRODUKSI LAK MELALUI PERBAIKAN SISTEM PEMUNGUTAN - Ishak Sumantri; Arifin Suzanto; Haryono Haryono (Jurnal Penelitian Hasil Hutan, 1989)
An investigation on lac cultivation was carried out in Probolinggo Forest District in September 1988. The purpose is to find possible ways of increasing the production. Host trees and methods for lac cultivation were observed. The results reveal that: Kesambi trees are good as the host for lac cultivation because they have sap density of 0.16 and sap reaction of 0.59 which which condition is favorable for lac survivals.Higher lac production can be obtained by using host trees that have many branches and twigs. Therefore, host trees need to be pruned in order to provide many new branches and twigs.Lacquor secretion yield can be harvested 5 months after lac cultivation. The lacquor production, thew is sorted intolacquor for cultivation and industrial materials. The cultivated lac can produce lacquor to the amount of three to five fold, depending on the quality of lac cu1tivated and the existance of diseases.